Silencing Constitutional Rights and Repressive Actions by the Authorities: A Comparative Criminal Law Analysis of Indonesia and Nepal - Elfa Murdiana; Lutfiana Dwi Mayasari; Ima Frafika Sari; Alendra Nauval M.R; Muhammad Talib Ibrahim (Universitas Lampung, 2025)
The policing of protests in Indonesia and Nepal, revealing systemic patterns of excessive force, arbitrary detention, and the criminalization of political expression. In Indonesia, the August 25–29, 2025 protests involved structured abuse of authority, including physical persecution, deprivation of liberty without adherence to Criminal Procedure Code protocols, and obstruction of legal counsel. In Nepal, 2025 protests saw the use of live ammunition, torture, and other severe measures violating the right to freedom of assembly under the 2015 Constitution. Both cases highlight legal deficiencies: Indonesia relies on general penal provisions without specialized instruments for state violations, while Nepal, despite criminalizing torture under Section 167 of the National Penal Code 2017, struggles with politically influenced implementation. Acts of violence and procedural abuse meet the criteria of unlawful acts, abuse of authority, and human rights violations under national and international law, including ICCPR and anti-torture standards. The failure to prosecute security personnel entrenches impunity. Findings indicate that strengthening accountability mechanisms, prosecuting officers when offenses are established, reforming security governance, and instituting independent investigative bodies are essential to protect constitutional rights and prevent recurrent state violence during protests.